A physically-based formulation for texture evolution during dynamic recrystallization. A case study of ice - Chauve, Thomas; Montagnat, Maurine; Dansereau, Véronique; Saramito, Pierre; Fourteau, Kévin; Tommasi, Andréa (Comptes Rendus. Mécanique)
Dynamic recrystallization can have a strong impact on texture development during the deformation of polycrystalline materials at high temperatures, particularly for materials with strong viscoplastic anisotropy such as ice. Owing to this anisotropy, recrystallization is essential for ensuring strain compatibility, and the development of textures leads to anisotropic softening. Accurate prediction of the effect of recrystallization on the texture evolution of ice is therefore crucial to adequately account for texture-induced mechanical anisotropy in large-scale models of glacial ice flow. However, this prediction remains a challenge.We propose a new formulation for modeling texture evolution due to dynamic recrystallization on the basis of observations of the evolution of the microstructure and texture of ice deforming by dislocation creep and dynamic recrystallization. This formulation relies on an orientation attractor that maximizes the resolved shear stress on the easiest slip system in the crystal. It is implemented in the equation describing the evolution of the crystal orientation with deformation and is coupled with an anisotropic viscoplastic law that provides the mechanical response of the ice crystal. This set of equations, which is the core of the R$^{3}$iCe model is solved by a finite-element method with a semi-implicit scheme coded using the Rheolef library. The resulting open-source software R$^{3}$iCe is validated by comparison with laboratory creep data for ice polycrystals under uniaxial compression, simple shear, and uniaxial tension. It correctly reproduces the texture evolution and mechanical softening observed in the experiment during tertiary creep. Although the present formulation is too time-consuming for direct implementation in large-scale ice flow models, R$^{3}$iCe can be used to adjust the parameterization used to implement texture-induced anisotropy in these models. The validation was performed for ice, but the R$^{3}$iCe implementation is generic and applies to any material whose behavior may be adequately described using an anisotropic flow law.